KETEKUNAN LATIHAN DAN KUALITAS HIDUP TIGA BULAN PASCA SERANGAN STROKE ISKEMIK - Sukarsi Rusti; Helda Helda; Sudarto Ronoatmodjo (LLDIKTI Wilayah X, 2023)
BACKGROUND: QUALITY OF LIFE OF STROKE PATIENTS IS AN IMPORTANT PART OF KNOWING THE EFFECTS OF STROKE. QUALITY OF LIFE ASSESSMENT CAN BE A REFERENCE FOR APPROPRIATE TREATMENT, TREATMENT AND REHABILITATION STRATEGIES. STROKE IS ONE OF THE LEADING CAUSES OF DISABILITY ADJUSTED LIFE YEARS (DALY'S). ABOUT 50% OF STROKE SURVIVORS IN THE WORLD EXPERIENCE DISABILITY AFTER HAVING A STROKE. ISCHEMIC STROKE PATIENTS WITH PHYSICAL DISABILITIES REQUIRE THERAPY / EXCERCISE UNDER THE SUPERVISION OF HEALTH PROFESSIONALS. THE PERSEVERANCE OF PATIENTS DOING EXERCISES CAN IMPROVE THE QUALITY OF LIFE OF STROKE PATIENTS. THE PURPOSE OF THE STUDY WAS: TO ANALYZE THE EFFECT OF EXERCISE PERSISTENCE ON QUALITY OF LIFE DURING THREE MONTHS POST-STROKE. METHODOLOGY: THIS STUDY INVOLVED 155 FIRST-ATTACK ISCHEMIC STROKE PATIENTS WHO WERE HOSPITALIZED AT THE DR.DRS. M. HATTA BRAIN HOSPITAL (RSOMH) BUKITTINGGI IN JANUARY – FEBRUARY 2022. THIS STUDY WAS A LONGITUDINAL STUDY WITH A CROSSECTIONAL DESIGN. THE SAMPLE WAS FOLLOWED FOR THREE MONTHS BY OBSERVING VARIABLES OF EXERCISE PERSISTENCE AND QUALITY OF LIFE FOR 3 MONTHS POST-STROKE. THE ANALYSIS IN THIS STUDY USED GENERALIZED ESTIMATING EQUATIONS. RESULTS: THERE ARE FIVE PHYSICAL DOMAINS MEASURED IN THIS STUDY AND IMPROVED, NAMELY THE DOMAINS: MOBILITY, SELF-CARE, PRODUCTIVITY, UPPER EXTREMITY FUNCTION, AND ENERGY. ISCHEMIC STROKE PATIENTS WHO DILIGENTLY FOLLOW EXERCISE ARE 2.5 TIMES MORE LIKELY (OR=2.5; 95%CI:1.3 - 4.7)